What Drives Media Use in Authoritarian Regimes? Extending Selective Exposure Theory to Iran - Wojcieszak, Magdalena and Nisbet, Erik C. and Kremer, Lea and Behrouzian, Golnoosh and Glynn, Carroll (The International Journal of Press/Politics, 2019)
Most work on selective exposure comes from the United States or other western democracies and typically examines partisan attitudes as the cognitive or motivational drivers of selectivity. This study extends the boundary conditions of existing literature by studying the factors affecting media choice in the Islamic Republic of Iran, a drastically understudied context. Within the overarching framework of motivated reasoning, we propose two theoretically relevant factors that should drive selective exposure into regime media or non-regime alternatives in authoritarian contexts: (1) system-justifying attitudes and (2) regime-sanctioned identities, here religiosity. Relying on two different surveys conducted within Iran in 2012 and 2016, we find that religiosity strongly predicts the reliance on non-regime media in both studies, whereas system-justifying attitudes predict selectivity in Study 2. Theoretical implications for the selectivity literature are discussed.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xOTQwMTYxMjE4ODA4Mzcy